2018
DOI: 10.1186/s12871-018-0545-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with intravenous lidocaine in pediatric patients undergoing laparoscopic appendectomy – a retrospective, single-centre experience

Abstract: BackgroundDue to its potential beneficial effects, intra- and postoperative application of intravenous lidocaine has become increasingly accepted over the last couple of years, e.g. in patients undergoing laparoscopic surgical procedures. Based on its beneficial properties, lidocaine was introduced to the standard of care for all pediatric laparoscopic procedures in our institution in mid-2016. In contrast to adult care, scarce data is available regarding the use of perioperative intravenous lidocaine administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 29 publications
(31 reference statements)
1
19
0
1
Order By: Relevance
“…Our study did not reveal any signs of anaphylaxis, systemic toxicity, circulatory disturbances or neurological impairment. This observation is consistent with other trials [3,5,6,14,15,22] investigating the issue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study did not reveal any signs of anaphylaxis, systemic toxicity, circulatory disturbances or neurological impairment. This observation is consistent with other trials [3,5,6,14,15,22] investigating the issue.…”
Section: Discussionsupporting
confidence: 92%
“…The aforementioned toxic thresholds are far above the concentrations recorded in El-Deeb's protocol of infusion administration. In light of these considerations as well as other data available in the literature [6,22] the proposed scheme of dosage was regarded as safe and chosen for investigation in our study. It was also approved by the Ethics Committee of the Medical University of Warsaw.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment attenuated the increase in serum cortisol levels, reduced daily fentanyl requirements, hastened the return of bowel functions, and reduced the length of the hospital stay for the children [12]. The other published study indicated that lidocaine (1.5 mg kg −1 over five minutes followed by 2 mg kg −1 h −1 ) decreased postoperative vomiting in children undergoing an elective tonsillectomy [13]. The serum’s lidocaine concentration was measured in both studies, and in no cases were toxic plasma concentration, neurological disturbances (seizures, numbness, tingling, or paresthesia), or cardiovascular collapses detected in any of the participants [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…The serum’s lidocaine concentration was measured in both studies, and in no cases were toxic plasma concentration, neurological disturbances (seizures, numbness, tingling, or paresthesia), or cardiovascular collapses detected in any of the participants [12,14]. University Children’s Hospital Zurich, Switzerland implemented the protocol of intravenous lidocaine infusion for children undergoing laparoscopic surgery, and adverse effects were not reported [13]. According to the Cochrane analysis, in adults undergoing open or laparoscopic abdominal surgery, a continuous lidocaine infusion rate of 1.5 mg kg −1 h −1 reduced pain immediately after, and until 24 h, with no increased risk of adverse effects such as death, arrhythmias or signs of lidocaine toxicity [15].…”
Section: Discussionmentioning
confidence: 99%